2009
DOI: 10.1007/s11355-009-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Fish habitat rehabilitation using wood in the world

Abstract: To provide river managers and researchers with practical knowledge about fish rehabilitation, various studies of fish habitat rehabilitation that used wood were reviewed. The review focuses on fish responses, wood installation methods, and geomorphic features of the rehabilitation sites. Most studies were conducted in moderately sized (small and medium) streams with relatively high bed gradients and aimed to improve the habitats of salmonid species. In this stream type, structures spanning the full (log dam) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 87 publications
1
49
0
Order By: Relevance
“…holding and cover for hiding Nagayama and Nakamura 2010). Greater wood abundance increases the overall number of pools (Beechie and Sibley 1997;Montgomery et al 1995), pool area (Beechie and Sibley 1997), and residual pool depth (Collins et al 2002) and can change the overall channel morphology from plane bed to forced-pool riffle channels (Buffington and Montgomery 1999;Montgomery et al 1996).…”
Section: Wood Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…holding and cover for hiding Nagayama and Nakamura 2010). Greater wood abundance increases the overall number of pools (Beechie and Sibley 1997;Montgomery et al 1995), pool area (Beechie and Sibley 1997), and residual pool depth (Collins et al 2002) and can change the overall channel morphology from plane bed to forced-pool riffle channels (Buffington and Montgomery 1999;Montgomery et al 1996).…”
Section: Wood Functionmentioning
confidence: 99%
“…In the Columbia River Basin of the Pacific Northwest, the focus of a large habitat restoration program, at least 2000 wood placement projects have been implemented since 1980 (National Oceanic and Atmospheric Administration (NOAA), unpublished data). Wood placement has also become commonplace in Europe, Japan, Australia, and other parts of the world (Brooks 2006;Nagayama and Nakamura 2010;Reich et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we need to develop installation methods and configurations of log jams that can serve to maintain fish habitats, and we need to recognize that engineered log jams can be used as a tool for interim habitat rehabilitation. Moreover, in rivers where physical conditions are unstable and sediment production is abundant, a greater consideration of the hydrogeomorphic conditions will be needed for success in rehabilitation projects (Shields et al, 2006;Nagayama & Nakamura, 2010).…”
Section: Implications For Habitat Restorationmentioning
confidence: 99%
“…Instream large wood plays an important role in shaping the distribution and composition of fish assemblages (Dolloff & Warren, 2003;Zalewski et al, 2003), as shown by many previous studies on the habitat of salmon in small streams (Zalewski et al, 2003;Nagayama & Nakamura, 2010). In contrast, there are few studies on other fish species, particularly in large rivers where the channel width is greater than the length of wood pieces (Murphy et al, 1989;Nagayama & Nakamura, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation